Method for dry-process acid modification of lithium-rich manganese-based positive electrode material and application of lithium-rich manganese-based positive electrode material
By using a dry acid modification method, solid acid powder and hydrated salt compounds are calcined at low temperature to produce lithium-rich manganese-based cathode materials. This solves the problems of high cost and acid wastewater treatment associated with wet acid modification, and achieves efficient electrochemical performance improvement and environmentally friendly modification.
Patent Information
- Application Number
- CN202411140409.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-01-10
AI Technical Summary
Existing lithium-rich manganese-based cathode materials suffer from low initial efficiency, large irreversible capacity loss, and high cost and acid wastewater treatment issues in wet acid modification processes, which limit their industrial application.
A dry acid modification method was adopted, which uses solid acid powder and hydrated salt compounds to work together. The exchange of lithium ions and hydrogen ions is achieved through low-temperature calcination, avoiding the generation of acid wastewater and optimizing electrochemical performance.
It reduces production costs, improves the first-efficiency and electrochemical performance of lithium-rich manganese-based cathode materials, and achieves a green and environmentally friendly acidification modification effect.
Smart Images

Figure HDA0005000617480000011 
Figure HDA0005000617480000012 
Figure HDA0005000617480000021
Abstract
Description
Technical Field
[0001] The present invention relates to a method for dry-process acid-modified lithium-rich manganese-based positive electrode material and application thereof, and relates to H01M, and specifically to the field of methods or devices for directly converting chemical energy into electrical energy. Background Art
[0002] With the popularization of new energy vehicles, the development of high energy density power batteries has gradually become an important research and development direction. The high discharge specific capacity of lithium-rich manganese-based positive electrode materials has attracted widespread attention, but the existing lithium-rich manganese-based positive electrode materials have low initial efficiency and large irreversible capacity loss. In order to improve the initial efficiency of lithium-rich manganese-based positive electrode materials, an acid modification method can be used. The existing acid modification methods mostly use wet acid modification, but they require corresponding wet reaction equipment and wastewater treatment. The corrosion of acidic solutions to equipment and other problems lead to high costs for industrial applications, which limits industrial development.
[0003] Chinese invention patent CN115763688A discloses a lithium-rich manganese-based positive electrode material and a preparation method thereof. The surface modification and calcination of the active material with a telluric acid source can synergistically improve the electrochemical properties of the active material. However, telluric acid needs to be prepared into an aqueous solution first, which produces acid wastewater. Chinese invention patent CN107215900B discloses a method for constructing a spinel structure on the surface of a lithium-rich manganese-based positive electrode material. By adjusting the concentration of the weak acid and the treatment time, the depth of the constructed spinel layer can be effectively adjusted, thereby adjusting the electrochemical properties of the electrode material, and the repetitive reliability is high. However, it is also a wet acid modification process, and the process treatment cost is high. Summary of the invention
[0004] In order to optimize the acid modification process of lithium-rich manganese-based positive electrode materials, the first aspect of the present invention provides a dry acid modification method for lithium-rich manganese-based positive electrode materials, comprising the following steps:
[0005] S1: Preparing a precursor: preparing a salt solution in a certain proportion, then adding a strong alkali solution and ammonia water, introducing an inert gas for protection, controlling the reaction temperature, time, and pH to perform a co-precipitation reaction, and then filtering, washing, and drying the precipitate to obtain a lithium-rich manganese-based precursor;
[0006] S2 primary calcination: mixing the lithium-rich manganese-based precursor with the lithium salt, calcining, introducing air, crushing the sintered product, and sieving to obtain a primary calcined product of the lithium-rich manganese-based positive electrode material;
[0007] S3 secondary roasting: the first fired product of the lithium-rich manganese-based positive electrode material is mixed with the solid acid powder, and then a low-temperature dehydrating agent is added, mixed at high speed, loaded in a sagger, and roasted for the second time;
[0008] S4 crushing and screening: crushing and screening the sintered product after roasting in step S3 to obtain a lithium-rich manganese-based positive electrode material.
[0009] As a preferred embodiment, the salt solution contains at least Li, Co, and Mn, and the molar ratio of Li, Co, and Mn is (0.2-0.5):(0-0.2):(0.5-1.0).
[0010] As a preferred embodiment, the molar ratio of Li, Co and Mn is (0.2-0.35):(0.1-0.15):(0.5-0.7).
[0011] As a preferred embodiment, the molar ratio of Li, Co and Mn is 0.26:0.15:0.59.
[0012] As a preferred embodiment, the concentration of the salt solution is 1-3 mol / L, the strong alkali solution is selected from one of NaOH and KOH, the concentration of NaOH is 4-12 mol / L, and the concentration of the ammonia water is 0-10 mol / L.
[0013] As a preferred embodiment, the salt solution includes NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O.
[0014] As a preferred embodiment, the concentration of the salt solution is 1.4 mol / L, the strong alkali solution is a NaOH solution, the concentration of the NaOH is 5 mol / L, and the concentration of the ammonia water is 5 mol / L.
[0015] As a preferred embodiment, in step S1, the reaction temperature is 10-80°C, the reaction time is 20-40h, and the pH is 9-12.
[0016] As a preferred embodiment, in step S1, the reaction temperature is 60° C., the reaction time is 35 h, and the pH is 11.
[0017] As a preferred embodiment, the lithium salt is selected from one or a combination of Li2CO3 and LiOH, and the molar ratio of the lithium-rich manganese-based precursor to the lithium salt is (1.03-1.2):1.
[0018] As a preferred embodiment, the lithium salt is Li2CO3. The molar ratio of the lithium-rich manganese-based precursor to the lithium salt is 1.1:1.
[0019] As a preferred embodiment, the primary calcination temperature is 800-980° C., and the primary calcination time is 8-18 hours.
[0020] As a preferred implementation manner, the primary calcination temperature is 900° C. and the primary calcination time is 10 h.
[0021] As a preferred embodiment, the chemical formula of the calcined product of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiNi 0.5 Mn 0.5 O2, where 0.1<x<0.5.
[0022] As a preferred embodiment, the chemical formula of the calcined product of the lithium-rich manganese-based positive electrode material is 0.33Li2MnO3·0.67LiNi 0.5 Mn 0.5 O2.
[0023] As a preferred embodiment, the mass ratio of the sintered lithium-rich manganese-based positive electrode material to the solid acid powder is 1:(0.01-0.1); the solid acid powder is selected from one or a combination of NH4Cl, NH4F, trichloroacetic acid, periodic acid, ethylenediaminetetraacetic acid, and citric acid.
[0024] As a preferred embodiment, the mass ratio of the sintered product of the lithium-rich manganese-based positive electrode material to the solid acid powder is 1:(0.02-0.04).
[0025] As a preferred implementation manner, the mass ratio of the sintered product of the lithium-rich manganese-based positive electrode material to the solid acid powder is 1:0.02.
[0026] As a preferred embodiment, the low-temperature dehydrating agent is a hydrated salt compound, and the hydrated salt compound is selected from one or a combination of KAl(SO4)2·12H2O, Na2SO4·10H2O, Na2CO3·10H2O, NiSO4·6H2O, CoSO4·7H2O, and CoCl2·6H2O; the mass of H2O in the hydrated salt compound accounts for 0.5%-2% of the mass of the sintered lithium-rich manganese-based positive electrode material.
[0027] As a preferred embodiment, the mass of H2O in the hydrated salt compound accounts for 1%-1.5% of the mass of the calcined lithium-rich manganese-based positive electrode material.
[0028] As a preferred embodiment, the mass of H2O in the hydrated salt compound accounts for 1.5% of the mass of the calcined lithium-rich manganese-based positive electrode material.
[0029] As a preferred embodiment, the secondary roasting is a staged roasting, first at a low temperature of 50-100°C, kept warm for 8-15h, then heated to 300-800°C, kept warm for 3-10h.
[0030] As a preferred embodiment, the secondary calcination is a staged calcination, first at a low temperature of 80°C, kept warm for 10 hours, then heated to 400-450°C, kept warm for 6-8 hours.
[0031] As a preferred embodiment, the secondary calcination is a staged calcination, first at a low temperature of 80° C., kept warm for 10 hours, then heated to 400° C., kept warm for 8 hours.
[0032] As a preferred embodiment, a ceramic cover is used on the sagger to reduce water evaporation. Low-temperature and long-term calcination can release the crystal water, and the water is attached to the particle surface for as long as possible to extend the modification time.
[0033] During the experiment, the applicant found that the wet method for acid modification of lithium-rich manganese-based positive electrode materials requires the treatment of a large amount of wastewater, and the waste acid solution is corrosive to the equipment and process pipelines, so the cost of wet acid modification is relatively high. In the traditional process, an acid solution is used to react with the positive electrode material, and the acid modification of the positive electrode material is achieved through the exchange of hydrogen ions and lithium ions. The applicant uses solid acid powder and hydrated salt compounds to act together. During the reaction, the hydrated salt compound, the solid acid and the lithium-rich manganese-based positive electrode material are evenly mixed. Under low temperature conditions, the hydrated salt compound is dehydrated to make the material moist, and hydrogen ions and lithium ions are exchanged to achieve the acid modification of the lithium-rich manganese-based positive electrode material. It does not involve free water, and the removal of crystal water can be achieved through long-term low-temperature roasting. There is no need to generate a large amount of acidic wastewater, which is green and environmentally friendly.
[0034] The applicant further discovered that low-temperature calcination at 50-100°C can prolong the attachment time of crystal water on the surface of lithium-rich manganese-based positive electrode particles, prolong the acidification modification time, and further improve the acidification effect.
[0035] As a preferred embodiment, the sieve used for sieving in steps S2 and S4 is a 325-mesh sieve.
[0036] The second aspect of the present invention provides a lithium-rich manganese-based positive electrode material, which is prepared by the dry acid modification method.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The dry acid-modified lithium-rich manganese-based positive electrode material method of the present invention uses solid acid powder instead of acid solution, which reduces the generation of acid wastewater in the acid modification process, reduces production costs, and is green and environmentally friendly.
[0039] (2) The dry acid modification method of the lithium-rich manganese-based positive electrode material described in the present invention adopts the combined action of solid acid powder and hydrated salt compound, and the dry acid modification replaces the wet acid modification, thereby improving the initial effect of the lithium-rich manganese-based positive electrode material and optimizing the electrochemical performance of the positive electrode material.
[0040] (3) The dry acid-modified lithium-rich manganese-based positive electrode material method of the present invention comprises a secondary calcination process, first a low-temperature calcination and then a high-temperature calcination. The hydrated salt compound is dehydrated under low temperature conditions to make the material moist, thereby achieving acid modification of the lithium-rich manganese-based positive electrode material and improving the comprehensive electrochemical properties of the positive electrode material.
[0041] (4) In the dry acid-modified lithium-rich manganese-based positive electrode material method of the present invention, a ceramic cover is used on the sagger to reduce water evaporation, so that water adheres to the particle surface for as long as possible, thereby extending the modification time.
[0042] (5) The dry acid modification method of the lithium-rich manganese-based positive electrode material of the present invention adopts dry acid modification, and the capacity and first-effect performance achieve the same effect as the wet modification, which greatly reduces the cumbersome process and reduces the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is an electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1;
[0044] Figure 2 This is an electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 2;
[0045] Figure 3 This is an electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 3;
[0046] Figure 4 This is an electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 1;
[0047] Figure 5 The charge and discharge curves of the lithium-rich manganese-based positive electrode material prepared in Example 1-3 and Comparative Example 1 when applied to a battery;
[0048] Figure 6 The XRD patterns of the lithium-rich manganese-based positive electrode materials prepared in Examples 1-3 and Comparative Example 1 and applied to batteries are compared.
[0049] In the figure: a: Example 1; b: Example 2; c: Example 3; d: Comparative Example 1. DETAILED DESCRIPTION
[0050] Example 1
[0051] A method for dry acid modification of lithium-rich manganese-based positive electrode materials, comprising the following steps:
[0052] S1: Preparing a precursor: preparing a salt solution in a certain proportion, then adding a strong alkali solution and ammonia water, introducing an inert gas for protection, controlling the reaction temperature, time, and pH to perform a co-precipitation reaction, and then filtering, washing, and drying the precipitate to obtain a lithium-rich manganese-based precursor;
[0053] S2 primary calcination: mixing the lithium-rich manganese-based precursor with the lithium salt, calcining, introducing air, crushing the sintered product, and sieving to obtain a primary calcined product of the lithium-rich manganese-based positive electrode material;
[0054] S3 secondary calcination: the first calcined product of the lithium-rich manganese-based positive electrode material is mixed with the solid acid powder, and then a low-temperature dehydrating agent is added, mixed at high speed, loaded into a sagger, a ceramic cover plate is used on the sagger, and secondary calcination is performed;
[0055] S4 crushing and screening: crushing and screening the sintered product after roasting in step S3 to obtain a lithium-rich manganese-based positive electrode material.
[0056] The salt solution includes NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O, and the molar ratio of Li, Co, and Mn is 0.26:0.15:0.59.
[0057] The concentration of the salt solution is 1.4 mol / L, the strong alkali solution is a NaOH solution, the concentration of the NaOH is 5 mol / L, and the concentration of the ammonia water is 5 mol / L.
[0058] In step S1, the reaction temperature is 60° C., the reaction time is 35 h, and the pH is 11.
[0059] The lithium salt is Li2CO3. The molar ratio of the lithium-rich manganese-based precursor to the lithium salt is 1.1:1.
[0060] The primary calcination temperature is 850° C., and the primary calcination time is 12 hours.
[0061] The chemical formula of the calcined product of the lithium-rich manganese-based positive electrode material is 0.33Li2MnO3·0.67LiNi 0.5 Mn 0.5 O2.
[0062] The mass ratio of the lithium-rich manganese-based positive electrode material-sintered product to the solid acid powder is 1:0.04. The solid acid powder is NH4Cl.
[0063] The low-temperature dehydrating agent is Na2CO3·10H2O, and the mass of H2O in the Na2CO3·10H2O accounts for 1% of the mass of the calcined lithium-rich manganese-based positive electrode material.
[0064] The secondary calcination is a staged calcination, first at a low temperature of 80° C., kept warm for 10 hours, then heated to 450° C., kept warm for 6 hours.
[0065] The sieve used in steps S2 and S4 is a 325 mesh sieve. Figure 1 .
[0066] Example 2
[0067] A method for dry acid modification of lithium-rich manganese-based positive electrode materials, comprising the following steps:
[0068] S1: Preparing a precursor: preparing a salt solution in a certain proportion, then adding a strong alkali solution and ammonia water, introducing an inert gas for protection, controlling the reaction temperature, time, and pH to perform a co-precipitation reaction, and then filtering, washing, and drying the precipitate to obtain a lithium-rich manganese-based precursor;
[0069] S2 primary calcination: mixing the lithium-rich manganese-based precursor with the lithium salt, calcining, introducing air, crushing the sintered product, and sieving to obtain a primary calcined product of the lithium-rich manganese-based positive electrode material;
[0070] S3 secondary calcination: the first calcined product of the lithium-rich manganese-based positive electrode material is mixed with the solid acid powder, and then a low-temperature dehydrating agent is added, mixed at high speed, loaded into a sagger, a ceramic cover plate is used on the sagger, and secondary calcination is performed;
[0071] S4 crushing and screening: crushing and screening the sintered product after roasting in step S3 to obtain a lithium-rich manganese-based positive electrode material.
[0072] The salt solution includes NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O, and the molar ratio of Li, Co, and Mn is 0.33:0.1:0.57.
[0073] The concentration of the salt solution is 1.4 mol / L, the strong alkali solution is a NaOH solution, the concentration of the NaOH is 5 mol / L, and the concentration of the ammonia water is 5 mol / L.
[0074] In step S1, the reaction temperature is 60° C., the reaction time is 35 h, and the pH is 11.
[0075] The lithium salt is Li2CO3. The molar ratio of the lithium-rich manganese-based precursor to the lithium salt is 1.1:1.
[0076] The primary calcination temperature is 900° C., and the primary calcination time is 10 hours.
[0077] The chemical formula of the calcined product of the lithium-rich manganese-based positive electrode material is 0.24Li2MnO3·0.76LiNi 0.5 Mn 0.5 O2.
[0078] The mass ratio of the calcined product of the lithium-rich manganese-based positive electrode material to the solid acid powder is 1:0.03. The solid acid powder is NH4F.
[0079] The low-temperature dehydrating agent is CoCl2·6H2O, and the mass of H2O in the CoCl2·6H2O accounts for 1.5% of the mass of the calcined lithium-rich manganese-based positive electrode material.
[0080] The secondary calcination is a staged calcination, first at a low temperature of 80° C., kept warm for 10 hours, then heated to 450° C., kept warm for 6 hours.
[0081] The sieve used in steps S2 and S4 is a 325 mesh sieve. Figure 2 .
[0082] Example 3
[0083] A method for dry acid modification of lithium-rich manganese-based positive electrode materials, comprising the following steps:
[0084] S1: Preparing a precursor: preparing a salt solution in a certain proportion, then adding a strong alkali solution and ammonia water, introducing an inert gas for protection, controlling the reaction temperature, time, and pH to perform a co-precipitation reaction, and then filtering, washing, and drying the precipitate to obtain a lithium-rich manganese-based precursor;
[0085] S2 primary calcination: mixing the lithium-rich manganese-based precursor with the lithium salt, calcining, introducing air, crushing the sintered product, and sieving to obtain a primary calcined product of the lithium-rich manganese-based positive electrode material;
[0086] S3 secondary calcination: the first calcined product of the lithium-rich manganese-based positive electrode material is mixed with the solid acid powder, and then a low-temperature dehydrating agent is added, mixed at high speed, loaded into a sagger, a ceramic cover plate is used on the sagger, and secondary calcination is performed;
[0087] S4 crushing and screening: crushing and screening the sintered product after roasting in step S3 to obtain a lithium-rich manganese-based positive electrode material.
[0088] The salt solution includes NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O, and the molar ratio of Li, Co, and Mn is 0.26:0.15:0.59.
[0089] The concentration of the salt solution is 1.4 mol / L, the strong alkali solution is a NaOH solution, the concentration of the NaOH is 5 mol / L, and the concentration of the ammonia water is 5 mol / L.
[0090] In step S1, the reaction temperature is 60° C., the reaction time is 35 h, and the pH is 11.
[0091] The lithium salt is Li2CO3. The molar ratio of the lithium-rich manganese-based precursor to the lithium salt is 1.1:1.
[0092] The primary calcination temperature is 900° C., and the primary calcination time is 10 hours.
[0093] The chemical formula of the calcined product of the lithium-rich manganese-based positive electrode material is 0.33Li2MnO3·0.67LiNi 0.5 Mn 0.5 O2.
[0094] The mass ratio of the lithium-rich manganese-based positive electrode material-sintered product to the solid acid powder is 1:0.02. The solid acid powder is citric acid.
[0095] The low-temperature dehydrating agent is CoCl2·6H2O, and the mass of H2O in the CoCl2·6H2O accounts for 1.5% of the mass of the calcined lithium-rich manganese-based positive electrode material.
[0096] The secondary roasting is a staged roasting, first at a low temperature of 80° C., kept warm for 10 hours, then heated to 400° C., kept warm for 8 hours.
[0097] The sieve used in steps S2 and S4 is a 325 mesh sieve. Figure 3 .
[0098] Comparative Example 1
[0099] A method for dry acid modification of lithium-rich manganese-based positive electrode materials, comprising the following steps:
[0100] S1: Preparing a precursor: preparing a salt solution in a certain proportion, then adding a strong alkali solution and ammonia water, introducing an inert gas for protection, controlling the reaction temperature, time, and pH to perform a co-precipitation reaction, and then filtering, washing, and drying the precipitate to obtain a lithium-rich manganese-based precursor;
[0101] S2 primary calcination: mixing the lithium-rich manganese-based precursor with the lithium salt, calcining, introducing air, crushing the sintered product, and sieving to obtain the lithium-rich manganese-based positive electrode material.
[0102] The salt solution includes NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O, and the molar ratio of Li, Co, and Mn is 0.26:0.15:0.59.
[0103] The concentration of the salt solution is 1.4 mol / L, the strong alkali solution is a NaOH solution, the concentration of the NaOH is 5 mol / L, and the concentration of the ammonia water is 5 mol / L.
[0104] In step S1, the reaction temperature is 60° C., the reaction time is 35 h, and the pH is 11.
[0105] The lithium salt is Li2CO3. The molar ratio of the lithium-rich manganese-based precursor to the lithium salt is 1.1:1.
[0106] The primary calcination temperature is 900° C., and the primary calcination time is 10 hours.
[0107] The chemical formula of the calcined product of the lithium-rich manganese-based positive electrode material is 0.33Li2MnO3·0.67LiNi 0.5 Mn 0.5 O2. The product scanning electron microscope image is shown in Figure 4 .
[0108] Performance Testing
[0109] 1. The lithium-rich manganese-based positive electrode materials of Examples 1-3 and Comparative Example 1 were prepared into button batteries, and the specific capacity and initial efficiency were tested under the conditions of 2.3-4.55V and 1C=230mAh / g.
[0110] Button battery: The mass ratio of lithium-rich manganese-based positive electrode material, SP conductive agent, and PVDF binder is 92:4:4, the negative electrode uses metal lithium sheet, the diaphragm uses PP material diaphragm, the electrolyte uses carbonate as solvent and LiPF6 as solute, and is assembled into button batteries in a nitrogen environment in a glove box according to the existing method.
[0111] The test results are shown in Table 1; the charge and discharge curves are shown in Figure 5 , XRD pattern see Figure 6 .
[0112] Table 1
[0113] project Example 1 Example 2 Example 3 Comparative Example 1 <![CDATA[Charge / mAhg -1 > 266.4 250.4 234.8 275 <![CDATA[Discharge / mAhg -1 > 212.9 219 212.7 204.8 efficacy / % 79.92 87.46 90.6 74.48
Claims
1. A method for dry acid modification of lithium-rich manganese-based positive electrode materials, characterized in that: The following steps are involved: S1: Preparing a precursor: preparing a salt solution in a certain proportion, then adding a strong alkali solution and ammonia water, introducing an inert gas for protection, controlling the reaction temperature, time, and pH to perform a co-precipitation reaction, and then filtering, washing, and drying the precipitate to obtain a lithium-rich manganese-based precursor; S2 primary calcination: mixing the lithium-rich manganese-based precursor with the lithium salt, calcining, introducing air, crushing the sintered product, and sieving to obtain a primary calcined product of the lithium-rich manganese-based positive electrode material; S3 secondary roasting: the first fired product of the lithium-rich manganese-based positive electrode material is mixed with the solid acid powder, and then a low-temperature dehydrating agent is added, mixed at high speed, loaded in a sagger, and roasted for the second time; S4 crushing and screening: crushing and screening the sintered product after roasting in step S3 to obtain a lithium-rich manganese-based positive electrode material.
2. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The salt solution contains at least Li, Co, and Mn, and the molar ratio of Li, Co, and Mn is (0.2-0.5):(0-0.2):(0.5-1.0).
3. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: In step S1, the reaction temperature is 10-80° C., the reaction time is 20-40 hours, and the pH is 9-12.
4. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The lithium salt is selected from one or a combination of Li2CO3 and LiOH, and the molar ratio of the lithium-rich manganese-based precursor to the lithium salt is (1.03-1.2):
1.
5. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The primary calcination temperature is 800-980° C., and the primary calcination time is 8-18 hours.
6. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The chemical formula of the calcined product of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiNi 0.5 Mn 0.5 O2, where 0.1<x<0.
5.
7. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The mass ratio of the calcined product of the lithium-rich manganese-based positive electrode material to the solid acid powder is 1:(0.01-0.1); the solid acid powder is selected from one or a combination of NH4Cl, NH4F, trichloroacetic acid, periodic acid, ethylenediaminetetraacetic acid, and citric acid.
8. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The low-temperature dehydrating agent is a hydrated salt compound, which is selected from one or a combination of KAl(SO4)2·12H2O, Na2SO4·10H2O, Na2CO3·10H2O, NiSO4·6H2O, CoSO4·7H2O, and CoCl2·6H2O; the mass of H2O in the hydrated salt compound accounts for 0.5%-2% of the mass of the sintered lithium-rich manganese-based positive electrode material.
9. The method for dry acid modification of lithium-rich manganese-based positive electrode materials according to claim 1, characterized in that: The secondary roasting is a staged roasting, which is first performed at a low temperature of 50-100° C., kept warm for 8-15 hours, and then heated to 300-800° C., kept warm for 3-10 hours.
10. A lithium-rich manganese-based positive electrode material, characterized in that: The invention is prepared by the dry acid modification method described in any one of claims 1 to 9.
Citation Information
Patent Citations
A method for constructing spinel structures on the surface of lithium-rich manganese-based cathode materials
CN107215900B
Lithium-rich manganese-based positive electrode material and preparation method thereof
CN115763688A